2005
DOI: 10.3171/jns.2005.102.4.0629
|View full text |Cite
|
Sign up to set email alerts
|

Is gross-total resection sufficient treatment for posterior fossa ependymomas?

Abstract: Gross-total resection should be the intent of surgery when it can be accomplished with an acceptable degree of morbidity. Even after GTR has been confirmed with postoperative imaging, however, adjuvant radiotherapy significantly improves local control. The authors currently recommend the use of postoperative radiotherapy, regardless of whether the resection is gross total or subtotal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…A retrospective study of ependymoma patients from the Barrow Neurological Institute included 73% of the cohort greater than 18 years of age. The study found a 10 year local control rate of 100% for patients who underwent a gross total resection followed by radiation versus 50% for those who underwent gross total resection alone (P = 0.018) [3]. The heterogeneity in the utilization of post-operative radiation therapy in adults seen in this study is likely a result of patients not receiving care in a multi-disciplinary setting.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A retrospective study of ependymoma patients from the Barrow Neurological Institute included 73% of the cohort greater than 18 years of age. The study found a 10 year local control rate of 100% for patients who underwent a gross total resection followed by radiation versus 50% for those who underwent gross total resection alone (P = 0.018) [3]. The heterogeneity in the utilization of post-operative radiation therapy in adults seen in this study is likely a result of patients not receiving care in a multi-disciplinary setting.…”
Section: Discussionmentioning
confidence: 94%
“…In the US, the current standard of care includes surgery with the goal of gross-total resection followed by post-operative irradiation using doses ranging from 54 to 59.4 Gy [2,3]. Past concerns regarding the long-term effects of irradiation in young children have led researchers to examine ways to delay or avoid its use in young children [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Gross total resection is more commonly achieved in supratentorial than in infratentorial ependymomas. The importance of thorough resection is well documented [1,4,7,10,11,12,13,14,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiotherapy following gross total resection of a posterior fossa ependymoma has been suggested to be beneficial in retrospective reviews [13,16], but adjuvant radiotherapy has not been subjected to the rigors of a randomized trial and thus remains disputable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation